Evaluasi Kinerja Pelayanan Angkutan Perdesaan (Studi Kasus : Trayek Cililin-Baranangsiang Kabupaten Bandung Barat) - Sansan Sanja Aprialdi; Mohamad Donie Aulia (Majalah Ilmiah UNIKOM, 2023)
Rural transportation in Indonesia experiences various obstacles such as poor infrastructure, inadequate services, less comprehensive coverage of rural public transportation. In accordance with the Decree of the Minister of Transportation No, 15 of 2019 concerning rural transportation to serve the needs of transportation transportation from one place to another in one district area that does not intersect in urban transportation routes. The purpose of this study is to determine the service performance and level of passenger satisfaction of rural transportation on the Cililin-Baranangsiang and Baranangsiang-Cililin routes. The research method used is to evaluate based on indicators of applicable public transportation service standard parameters and passenger perception. The analysis results show that for Headway service indicators on weekdays, including the medium category with the average headway value on the Cililin-Baranangsiang route is 12.92 minutes and Baranangsiang-Cililin is 14.05 minutes. Headway on weekend days, including the less category with the average value of headway performance obtained on the Cililin-Baranangsiang route is 17.82 minutes and Baranangsiang-Cililin is 18.82 minutes. Load Factor on weekdays, including the category meets the standards with the average value of load factor obtained on the Cililin-Baranangsiang route is 77.08% and the Baranangsiang-Cililin route is 80.56%. Load Factor on weekend days, including the category of not meeting the standard with the average value of load factor obtained on the Cililin-Baranangsiang route is 61.11% and the Baranangsiang-Cililin route is 63.19%, Speed on weekdays, including the category meets the standards with the average value of rural transportation vehicles on the Cililin-Baranangsiang route is 23.15 km / hour and the Baranang-siang-Cililin route is 23.43 km / hour. The speed on weekend days, including the category meets the standard with the average speed value of rural transportation vehicles on the Cililin-Baranangsiang route is 23.43 km / hour and the Baranangsiang-Cililin route is 23.33 km / hour. According to respondents, the services provided by rural transportation on the Cililin-Baranangsiang route and the Baranangsiang-Cililin route are quite good, but bad for indicators of waiting time, availability of rural transportation fleets, noise and travel time. Some of these indicators need to be improved so that rural transportation services in West Bandung Regency become better. Key Words: Evaluation, Performance, Headway, Load Factor, Speed, Satisfaction